EARTHQUAKE PREDICTION IN THE AREA OF N. EVIA ON THE BASIS OF GROUNDWATER RADON CONCENTRATION CHANGES - Μητρόπουλος Π.; Notsu, K.; Δελήμπασης Ν.; Κακαβάς N.; Βουδούρης Π. (Bulletin of the Geological Society of Greece, 2004)
Significant changes in the groundwater radon concentration, were observed on the 29/7/2003, at Kammena Vourla. The radon concentration changes can be attributed to the temporary enrichment of the groundwater by radon from the surrounding rocks due to the action of stress release or stress accumulation prior an earthquake. EPPO was immediately informed for the existence of these changes. On the 3/8/2003, a significant number of earthquakes in Northern Evia were recorded in an interval of a few hours. The epicentres of the earthquakes were located in the conceivable line between the epicentre of the strong earthquake of Skyros island (July 2001) and the site of the station of radon measurement at Kammena Vourla, on the extension of the Northern Aegean fault. In the 23/1/2003, in the same station, 3 significant changes of radon concentration were measured EPPO was immediately informed for impending seismic activity in Northern Evia. On the 29th of January three earthquakes were recorded. Their epicentres were located in N. Evia, close to the radon measurement, station. On the 2/2/2003, a new significant radon change occurred at Kammena Vourla followed by an earthquake (7/2/2003). In the 12/2/2003 in a letter that we addressed to the EPPO administration, the beginning of a new radon change was reported which also led to an earthquake with the same epicentre. The changes that are recorded in the system of radon measurement of Kammena Vourla are precursors of earthquakes, related to the extension of the N. Aegean fault towards the Sterea Hellas and have their epicentre in N. Evia. It seems that the method can be an important tool for local, short term earthquake prediction.